Unanticipated switch of reactivity of isonitrile via N≡C bond scission: Cascade formation of symmetrical sulfonyl guanidine - Debashish Mishra; Sagarika Rajkhowa; Prodeep Phukan (iScience, 2023)
Summary: Unanticipated formation of symmetrical sulfonyl guanidine was observed while treating isonitriles with N,N-dibromoarylsulfonamides in absence of an external amine source. Interesting feature of this work is that one molecule of isonitrile initially reacts with dibromoarylsulfonamide via the C-end to produce the intermediate carbodiimide while the other molecule undergoes C≡N triple bond cleavage to react as amine source with the intermediate. This switch of reactivity from C-center to N-center of the isonitrile generated symmetrical guanidine.